Independent filmmaking around the globe - Erickson, Mary, 1977-; Baltruschat, Doris (University of Toronto Press, 2015)
With chapters on under-explored cinemas as well as traditional centres, Independent Filmmaking around the Globe explores how contemporary independent filmmaking increasingly defines the global cinema of our time.